EDUKASI PENGENALAN JENIS RADANG SENDI BERDASARKAN GEJALA DAN PENCEGAHANNYA - Birman, Yuliza; Rosmaini, Rosmaini; Suharni, Suharni; Dhina Auliya Khairina; Intana Liyu (Nusantara Hasana Journal, 2024)
Arthritis is a disease that is often suffered not only by the elderly but also by young people. There are various types of arthritis, including osteoarthritis, breumatoid arthritis and gouty arthritis. These three types of arthritis differ in terms of the specifications of symptoms and causes. By recognizing the type of arthritis based on symptoms, we can prevent the severity of arthritis. For that, we from the Faculty of Medicine, Baiturrahmah University provide education to the community at the Lubuk Begalung Padang District Office within the framework of the Medical Baiturrahmah Social Action (MBSA) event which is routinely held every year involving lecturers and students.